Immunofluorescence and histopathological assessment using ex vivo confocal laser scanning microscopy in lichen planus. Issue 12 (26th October 2020) - Bağcı, Işın Sinem; Aoki, Rui; Krammer, Sebastian; Vladimirova, Gabriela; Ruzicka, Thomas; Sárdy, Miklós; French, Lars E.; Hartmann, Daniela
Abstract: Ex vivo confocal laser scanning microscopy (CLSM) provides rapid, high‐resolution imaging, fluorescence detection and digital haematoxylin–eosin (H&E)‐like staining. We aimed to assess the performance of ex vivo CLSM in identifying histomorphology and immunoreactivity in lichen planus (LP) and comparing its accuracy with conventional histopathology and direct immunofluorescence (DIF). Thirty‐three sections of 17 LP patients stained with acridine orange (AO) and FITC‐labelled anti‐fibrinogen antibody and 21 control samples stained with AO were examined using ex vivo CLSM. Ex vivo CLSM was in perfect agreement with conventional histopathology in identifying interface dermatitis, vacuolar degeneration and band‐like infiltration. ROC analysis showed that the presence of vacuolar degeneration, interface dermatitis and band‐like infiltration was useful to distinguish LP sections from controls ( p  < .0001). The detection rates of fibrinogen deposition using DIF and in conclusion ex vivo CLSM were 93.8% and 62.5%, respectively. ex vivo CLSM enables histopathological and immunofluorescence examination in LP with the advantage of digital H&E‐like staining. Abstract : In this study, we assessed the performance of ex vivo confocal laser scanning microscopy (CLSM) in identifying histomorphological and immunofluorescence features of lichen planus (LP). Ex vivo CLSM showed a perfect agreement with conventional histopathology in identifying key features of LP namely interface dermatitis, vacuolar degeneration and band‐like infiltration. Ex vivo CLSM could detect fibrinogen deposition in 62.5% of the sections; whereas, conventional DIF detected fibrinogen deposition in 93.8% of the sections.